Hubungan Kecanduan Gadget dengan Gangguan Emosi dan Perilaku pada Remaja di Masa Pandemi - Natasya, Stella; Nurhajjah , Siti; Masnadi , Nice Rachmawati (Seroja Husada: Jurnal Kesehatan Masyarakat, 2024)
Gadget addiction can cause emotional and behavioral disordes in adolescents. Covid-19 pandemic, which began at the end of 2019, caused children to carry out online teaching and learning process from home. This causes an increased gadget addiction during the pandemic. This study aims to determine the relationship between the level of gadget addiction with emotional and behavioral disorders in adolescents during Covid-19 pandemic. This is an analytic study with a cross-sectional design. The research sample was 155 students of SMPN 10 Batang Hari, Jambi in 2021. Sampling technique used was proportional random sampling method for grade-level samples, and consecutive sampling method for class-level samples. Characteristic results was obtained from students personal data, the level of gadget addiction from Smartphone Addiction Scale – Short Version questionnaire, and the level of emotional and behavioral disorders from Strengths and Difficulties questionnaire. The data were analyzed using chi-square. High level of gadget addiction were dominated by students in group age of 11-14 years old (60.3%), and of female sex group (32.9%). High level of gadget addiction have emotional and behavioral disorders in normal category (28.4%), borderline category (19.4%), and abnormal category (14.2%). Adolescent with high gadget addiction are correlation with emotional and behavior disorders during pandemic (p=0.001) This study concluded that there is a relation between gadget addiction and emotional and beahvioral level in adolescent during the Covid-19 pandemic.